The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-635x2013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Balance of broilers fed diets containing two calcium levels and supplemented with different phytase levels

Abstract: The objective of this study was to evaluate the effect of diets containing different calcium and phytase levels on the nutritional balance of broilers.A total of 108 male AG Ross 308 broilers were used in each of the replicates phases used in the study: starter (1-21 days), grower (29-35 days) and finisher (36-42 days). A completely randomized experimental design in a 3 x 2 factorial arrangement, with three phytase levels (0, 600 or 1200 FTU/kg) and two calcium levels (0.94 and 0.66%; 0.84 and 0.59%; e 0.78 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Broilers fed the CON+PHY diet maintained live performance similar to the CON diet, which demonstrated that the PHY enzyme restored AvP and Ca to normal levels as reported by others (Donato et al, 2013;dos Santos et al, 2017;Walk & F. Poernama, 2018). However, no other nutritional benefits due to the PHY were observed.…”
Section: Discussionsupporting
confidence: 81%
“…Broilers fed the CON+PHY diet maintained live performance similar to the CON diet, which demonstrated that the PHY enzyme restored AvP and Ca to normal levels as reported by others (Donato et al, 2013;dos Santos et al, 2017;Walk & F. Poernama, 2018). However, no other nutritional benefits due to the PHY were observed.…”
Section: Discussionsupporting
confidence: 81%
“…Phytase supplementation in an isolated manner allows the reduction of crude protein and minerals, such as phosphorus, calcium, and sodium, in diets without compromising broiler performance (Lelis et al, 2010;Donato et al, 2011;Meneghetti et al, 2011). Although the reduction of nutrients is possible because of the higher metabolizability provided by the enzyme, calcium should be reduced proportionally to reduce the total phosphorus levels to avoid an increase in intestinal pH due to formation of calcium phytate and its interaction with iron, magnesium, and zinc and a reduction in phytase activity by high calcium concentrations (Schoulten et al, 2003).…”
Section: Introductionmentioning
confidence: 99%